Proteomic Landscape of Small Extracellular Vesicles Derived From Gastric Juice and Identified TFF2 as a Specific Biomarker - Fan R; Wu K; Yang J; Zhu B; Jiang T; Liu Y; Yuan B; Liu L; Sun Y; Sun X; Liu L; Luo W; et al. (International Journal of Nanomedicine)
Ruiling Fan,1,* Kaiwen Wu,2,* Jingwei Yang,1,* Binjun Zhu,3 Tao Jiang,3 Yu Liu,4 Bin Yuan,1 Lüye Liu,5 Yueshan Sun,5 Xiaobin Sun,6 Liu Liu,6 Wencai Luo,7 Chunyang Zhou,1 Yuanbiao Guo,5 Lei Liu5 1Institute of Materia Medica, School of Pharmacy, North Sichuan Medical College, Nanchong, Sichuan, 637007, People’s Republic of China; 2Department of Ultrasound, Shanghai Pulmonary Hospital, Tongji University School of Medicine, Shanghai, 200433, People’s Republic of China; 3North Sichuan Medical College, Nanchong, Sichuan, 637007, People’s Republic of China; 4Chinese Academy of Medical Science & Peking Union Medical College, Chengdu, Sichuan, 610052, People’s Republic of China; 5Medical Research Center, Affiliated Hospital of Southwest Jiaotong University, The Third People’s Hospital of Chengdu, Chengdu, Sichuan, 610014, People’s Republic of China; 6Department of Gastroenterology, Affiliated Hospital of Southwest Jiaotong University, The Third People’s Hospital of Chengdu, Chengdu, Sichuan, 610014, People’s Republic of China; 7Department of Gastroenterology, The People’s Hospital of Guanghan, Deyang, Sichuan, 618300, People’s Republic of China*These authors contributed equally to this workCorrespondence: Lei Liu, Medical Research Center, The Third People’s Hospital of Chengdu, The Affiliated Hospital of Southwest Jiaotong University, 82# Qinglong Street, Chengdu, Sichuan, 610014, People’s Republic of China, Email liulei@swjtu.edu.cn Yuanbiao Guo, Medical Research Center, The Third People’s Hospital of Chengdu, The Affiliated Hospital of Southwest Jiaotong University, 82# Qinglong Street, Chengdu, Sichuan, 610014, People’s Republic of China, Email guo.ybiao@yahoo.comIntroduction: Small extracellular vesicles (sEVs) derived from gastric juice (GJ) have emerged as potential biomarkers for gastric disease. However, methods for isolating sEVs from GJ (gsEVs) remain underexplored.Methods: This study employed four methods for isolating gsEVs: ultracentrifugation (UC), PEG6000 precipitation combined with UC (PEG-UC), UC combined with size exclusion chromatography (UC-SEC), and ultrafiltration combined with SEC (UF-SEC). The yield and purity of gsEVs isolated by each method were evaluated, and the proteomic profile of gsEVs was examined through label-free quantitative proteomics. Additionally, a series of validation experiments were conducted to identify specific biomarkers for gsEVs.Results: The results revealed that gsEVs isolated using the UC method exhibited the highest purity and the largest number of identified proteins compared to the other methods. Notably, the gastric tissue-specific peptide trefoil factor 2 (TFF2) was highly expressed in gsEVs isolated by all methods, suggesting that TFF2 may serve as a specific biomarker for gsEVs. Validation experiments showed that TFF2 was exclusively present in gsEVs and not in the GJ supernatant after UC. Furthermore, TFF2 was selectively expressed in gsEVs, but not in sEVs derived from other biofluids such as intestinal juice and plasma. The efficiency of TFF2 as a gsEVs biomarker was higher than the commonly used biomarker CD9, CD81, and Syntenin-1. Multi-omics analysis indicated that the functions of gsEVs carrying TFF2 were primarily associated with inflammation and cancer.Conclusion: The UC method is suitable for isolating gsEVs, particularly for mass spectrometry-based proteomic analysis. The small peptide TFF2 may serve as a potential specific biomarker for gsEVs. This study offers new insights for research on sEVs in gastric diseases.Keywords: gastric juice, small extracellular vesicles, proteomic, TFF2, biomarker